A Dynamical Interpretation of the Intensification of the Winter North Atlantic Jet Stream in Reanalysis - Hermoso, Alejandro; Gwendal, Rivière; Harvey, Ben; Methven, John; Schemm, Sebastian; id_orcid:0 000-0002-1601-5683 (American Meteorological Society, 2024)
ISSN:0894-8755 ISSN:1520-0442